Coming back from China to USA? - Filipe, J. A.; Ferreira, M. A. M.; Chavaglia, J. N.; Coelho, M. P.; Pedro, M. I. (International Journal of Academic Research, 2013)
A lot of international companies found in China the ideal place to install their factories. Many of them are coming yet to China, to a promised land, where costs are lower and economy is very competitive. China ability to penetrate in international markets much in consequence of the low production costs, in particular low wages, and the increasing internal market are making China one of the most powerful and influent economic countries. China has made a very coherent and consistent management of the economy, planned and visionary, including the management of natural resources and the Chinese development planning in general. This vision has contributed to guarantee the future development of China, and its economic and politic power. However, many companies are coming back to USA because they consider that the reduced costs (principally wages) in China are not anymore so attractive as before. An analysis of this new international scenario is made in this paper as much as a perspective for the future and the implications resulting from companies' investment movements.